2015
DOI: 10.1007/s10528-015-9698-5
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of GSTM1, GSTT1 and GSTP1 Gene Polymorphism to Breast Cancer Susceptibility in Mizoram Population, Northeast India

Abstract: The enzymes encoded by glutathione S-transferase mu 1 (GSTM1) and theta 1 (GSTT1) genes are involved in the metabolism of wide range of carcinogens that are ubiquitous in the environment. Homozygous deletions of the GSTM1 and GSTT1 genes are commonly found and result in lack of enzyme activity. This study was undertaken to evaluate the association between GSTM1, GSTT1 and GSTP1 gene polymorphism and breast cancer risk in Mizoram population. Odd ratio (OR) and 95% confidence interval (CI) from conditional logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
1
9
1
1
Order By: Relevance
“…Findings of this study are contrary to what have been seen among Indians (Kimi et al, 2016), Brazilians (Possuelo et al, 2013), Caucasians (Zheng et al, 2002), Dutch (van der Hel et al, 2004), and French (Lizard-Nacol et al, 1999. The lack of association of GSTM1 null genotype with breast cancer has also been seen in Iranian (Saadat et al, 2001), Lebanese (Zgheib et al, 2013), Pakistani (Sohail et al, 2013), Taiwanese (Chang et al, 2006), Icelandic (Gudmundsdottir et al, 2001), Mexican (Rodriguez et al, 2014), and Caucasian and African-American (Van Emburgh et al, 2008) populations.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Findings of this study are contrary to what have been seen among Indians (Kimi et al, 2016), Brazilians (Possuelo et al, 2013), Caucasians (Zheng et al, 2002), Dutch (van der Hel et al, 2004), and French (Lizard-Nacol et al, 1999. The lack of association of GSTM1 null genotype with breast cancer has also been seen in Iranian (Saadat et al, 2001), Lebanese (Zgheib et al, 2013), Pakistani (Sohail et al, 2013), Taiwanese (Chang et al, 2006), Icelandic (Gudmundsdottir et al, 2001), Mexican (Rodriguez et al, 2014), and Caucasian and African-American (Van Emburgh et al, 2008) populations.…”
Section: Discussioncontrasting
confidence: 98%
“…The lack of association between GSTT1 null genotype and breast cancer has been seen in Dutch (van der Hel et al, 2004), Lebanese (Zgheib et al, 2013), Pakistani (Sohail et al, 2013), Icelandic (Gudmundsdottir et al, 2001), Mexican (Rodriguez et al, 2014), Caucasian and African-American (Van Emburgh et al, 2008) and Iranian (Hashemi et al, 2012) populations. Association of GSTT1 null genotype with breast cancer have been observed in studies from Northeast India (Kimi et al, 2016), Iowa (Zheng et al, 2002, Southern Taiwan (Chang et al, 2006), and China (Tang et al, 2015;Xiao et al, 2015;Song et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, an association between the GSTP1 polymorphisms and BC has been found to be exacerbated by alcohol consumption (44). Many factors can be considered for the inconsistent findings, such as population differences, ethnic origin, lifestyle habits, smoking, and alcohol consumption (45). Furthermore, other genetic variations might be associated with the risk of BC; for instance, hypermethylation of the GSTP1 promoter has been associated with BC risk (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that GSTP1 polymorphism is associated with various kinds of cancers, such as acute myeloid leukemia, lung cancer, breast cancer, colorectal cancer, brain tumor, and esophageal cancer (Cong et al, 2014;Silva et al, 2014;Song et al, 2014;Jaramillo-Rangel et al, 2015;Nasr et al, 2015;Sharma et al, 2015;Soto-Quintana et al, 2015;Zhou et al, 2015;Geng et al, 2016;Khabaz et al, 2016;Kimi et al, 2016). Several studies have also reported that GSTP1 polymorphism is associated with risk of gastric cancer in various populations, but the results were inconsistent (Nguyen et al, 2010;Zhang et al, 2011;Bao et al, 2012;García-González et al, 2012;Jing et al, 2012;Zhang et al, 2012;Ma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%